A new Pseudophyllidean Senga rupchandensis n.sp. from Channa striatus (Bloch, 1793) at Jalna District (M.S.), India - C.J. Hiware*, P.R. Pardeshi and (Recent Research in Science and Technology, 2011)
The present communication deals with the description of a new species of genus Senga [3], viz Senga rupchandensis n.sp. from Mastacembelus armatus, Jayakwadi Dam, Paithan at Aurangabad District, the present form differ from the known species of the genus in the shape and size of the scolex, number of hooks and arrangement of rostellum, shape of segment, number of testes, position of cirrus pouch and arrangement of vitellaria.